Conjugate Meningococcal Vaccines Development: GSK Biologicals Experience - Miller, Jacqueline M. (SAGE-Hindawi Access to Research, 2011)
Meningococcal diseases are serious threats to global health, and new vaccines specifically tailored to meet the age-related needs of various geographical areas are required. This paper focuses on the meningococcal conjugate vaccines developed by GSK Biologicals. Two combined conjugate vaccines were developed to help protect infants and young children in countries where the incidence of meningococcal serogroup C or serogroup C and Y disease is important: Hib-MenC-TT vaccine, which offers protection against Haemophilus influenzae type b and Neisseria meningitidis serogroup C diseases, is approved in several countries; and Hib-MenCY-TT vaccine, which adds N. meningitidis serogroup Y antigen, is currently in the final stages of development. Additionally, a tetravalent conjugate vaccine (MenACWY-TT) designed to help protect against four meningococcal serogroups is presently being evaluated for global use in all age groups. All of these vaccines were shown to be highly immunogenic and to have clinically acceptable safety profiles.